2008
DOI: 10.1007/s00167-008-0498-x
|View full text |Cite
|
Sign up to set email alerts
|

Function, osteoarthritis and activity after ACL-rupture: 11 years follow-up results of conservative versus reconstructive treatment

Abstract: ACL-reconstruction aims to restore joint stability and prevent osteoarthritis; however, malfunction and osteoarthritis are often the sequelae. Our study asks whether ACL-reconstruction or conservative treatment lead to better long-term results. In this retrospective cohort study, 136 patients with isolated ACL-rupture who had been treated by bone-ligament-bone transplant or conservatively were identified. Twenty-seven of these were excluded because of a revision operation in the 11.1 years follow-up period, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
382
8
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(411 citation statements)
references
References 42 publications
11
382
8
10
Order By: Relevance
“…On the contrary, a study by Daniel et al showed a trend towards a greater prevalence of osteoarthritis in surgically-treated than in non-surgically treated patients [7]. Also Kessler et al reported on a significantly higher rate of osteoarthritis in patients 11 years following an operative treatment of ACL insufficiency [23]. In contrast to our investigation they excluded patients with meniscal injuries or chondral lesions, which rarely occur [24].…”
Section: Discussioncontrasting
confidence: 68%
“…On the contrary, a study by Daniel et al showed a trend towards a greater prevalence of osteoarthritis in surgically-treated than in non-surgically treated patients [7]. Also Kessler et al reported on a significantly higher rate of osteoarthritis in patients 11 years following an operative treatment of ACL insufficiency [23]. In contrast to our investigation they excluded patients with meniscal injuries or chondral lesions, which rarely occur [24].…”
Section: Discussioncontrasting
confidence: 68%
“…10 Many grafts function as mechanical springs that span the gap between the femur and tibia, providing stability and allowing joint motion, but do not complete the ligamentization process or restore the original biomechanics to the knee even 2-3 years after surgery. [8][9][10] In addition, the incidence of early-onset OA within 7-14 years after knee injury is as high as 50%, 5,11,12 without improved outcomes as a result of ACL reconstruction. 5,13 Thus, there is a need for a ligament graft that will develop biochemically relevant and biomechanically compatible interfaces with native tissue and restore the proper biomechanics and physiological function to the ligament.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Butler et al 12 tested participants an average of 5 years postoperatively, a time when radiographic osteoarthritis may be influencing lower extremity biomechanics. [24][25][26] When comparing KAM in the ACL þ BB and control groups with the ACL-injury group, we observed strong effect sizes with CIs that did not cross zero. These large effect sizes suggest that participants may have had clinically relevant differences in KAM.…”
Section: Discussionmentioning
confidence: 83%